Promising solid electrolyte material for an IT‐SOFC: crystal structure of the cerium gadolinium holmium oxide Ce0.8Gd0.1Ho0.1O1.9 between 295 and 1023 K. Issue 2 (30th January 2018) - Rahayu, Sri; Forrester, Jennifer S.; Kale, Girish M.; Ghadiri, Mojtaba
Abstract : Rietveld refinements of the powder X‐ray diffraction data of the electrolyte material Ce0.8 Gd0.1 Ho0.1 O1.9 show that it is a fluorite with the space group Fm m and that it has crystal structure stability from room temperature to elevated temperatures. Abstract : The crystal structure of Ce0.8 Gd0.1 Ho0.1 O1.9 (cerium gadolinium holmium oxide) has been determined from powder X‐ray diffraction data. This is a promising material for application as a solid electrolyte for intermediate‐temperature solid oxide fuel cells (IT‐SOFCs). Nanoparticles were prepared using a novel sodium alginate sol‐gel method, where the sodium ion was exchanged with ions of interest and, after washing, the gel was calcined at 723 K in air. The crystallographic features of Gd and Ho co‐doped cerium oxide were investigated around the desired operating temperatures of IT‐SOFCs, i.e. 573 ≤ T ≤ 1023 K. We find that the crystal structure is a stable fluorite structure with the space group Fm m in the entire temperature range. In addition, the trend in lattice parameters shows that there is a monotonic increase with increasing temperature.